Construction of Intercultural Savoirs Through Interculturally-laden Tasks: An Iranian Experience - داود کوهی; سیده زهرا اسماعیلی; ثریا بهروزی زاد (Journal of Applied Linguistics)
A long-standing concern reverberating over the minds of intercultural scholars is how best to incorporate intercultural issues in English language teaching, an issue on which there has been little research in EFL contexts. To fill this gap, this qualitative study examined the efficacy of interculturally-laden tasks in promoting Iranian learners’ intercultural competency in Anzali, Guilan province, Iran. Thus, a group of 22 Iranian intermediate EFL learners were recruited through convenience sampling from a pool of 44 according to their score on Oxford Quick Placement Test. All the participants were 12 females and 10 males aged 21-30. Then, they attended eighteen sessions of intercultural training using Mirrors and Windows: An intercultural communication textbook and completed seven intercultural tasks as a pretest and posttest. Data was collected through seven intercultural tasks and reflective worksheets. Drawing on the qualitative content analysis of intercultural tasks, the findings revealed that the tasks could help the participants increase their intercultural competence. Moreover, three themes were emerged from the analysis of the reflective worksheets as follow: (1) the participants’ evaluation of the ICC course and intercultural tasks, (2) perceptions regarding intercultural development and (3) language skills and anxiety. The implications and suggestions for further research are discussed.